PENILAIAN IT SERVICE MANAGEMENT PADA INFRASTRUKTUR TEKNOLOGI INFORMASI PT. TELKOM KOTA BENGKULU MENGGUNAKAN ITIL V3 - Mahdalena, Desi; Cholil, Widya (Vocational School Diponegoro University, 2020)
IT Service Management (ITSM) is a management concept in providing information technology services properly and successfully to customers, it can also be a method of processing philosophical systems that are centered on the IT service consumer perspective on the company's business. The service management of an organization is basically implemented in the form of the functions of the organization's functions (functions) and the processes that are carried out (processes) in managing and changing the resources (resources) of the organization into the values expected by the customer. ITIL or the summary of the Information Technology Infrastructure Library is a general framework that describes best practices that provide guidance on how Information Technology (IT) service providers should run IT service management. One of the organizations that provide IT services is PT. Telkom, which has an IndiHome application for customers who want to use internet or cable TV services. This research evaluates maturity level the information technology infrastructure that supports IndiHome's business processes at PT. Telkom Bengkulu. So that with this assessment can see the achievement of performance at PT. Telkom Bengkulu. The focus of this research is the domain service operation on ITIL V3.